Choosing fame over academia: Exploring the appeal of becoming a social media influencer. - Ibrahim, Norshamsiah; Mohd Adam Khan, Nur Shazweena Hani (Journal of Islamic, Social, Economics and Development, 2025)
This study explores the motivations of young people, in particular Generation Z, to choose career paths as social media influencers instead of pursuing in higher educational institutions. It analyses how the rapid rise of social media platforms has changed the career aspirations, offering an attractive alternative to formal education. This study proposes a conceptual framework to help elucidate the appeal of becoming an influencer, consisting of financial incentives, desire for fame and recognition, and flexibility and engagement of work. This conceptual paper provides the key insight for educators, policymakers and stakeholders, to adjust their pedagogical strategies in line with the developing digital career marketplaces. By encouraging digital learning and adhering to the current trends, educational institutions will be better able to equip students for success in a technology-driven world.